Micronutrient Intake in a Cohort of Italian Adults with Type 1 Diabetes: Adherence to Dietary Recommendations - Marisa Giorgini; Marilena Vitale; Lutgarda Bozzetto; Ornella Ciano; Angela Giacco; Anna Rivieccio; Ilaria Calabrese; Gabriele Riccardi; Angela A. Rivellese; Giovanni Annuzzi (Journal of Diabetes Research)
Micronutrients are of fundamental importance in maintaining health status. However, data on their dietary intake are few particularly in persons with diabetes. The aim of this study was to evaluate in adults with type 1 diabetes (T1DM) attending a tertiary-level diabetes center in Southern Italy the intake of micronutrients (both vitamins and minerals) and the adherence to recommendations. Seven-day food records of 60 T1DM patients were analyzed. Micronutrient intake was evaluated based on the Italian food composition tables and expressed as amount per 1000 kcal of energy intake to adjust for possible underreporting. Adherence to recommendations for vitamins A, B6, B12, and C and niacin was acceptable in both sexes (ranging from 77% to 100%). Half of the patients did not adhere to folate recommendation, even less to vitamin E, and no patient reached the recommended intake for vitamin D. As for minerals, adherence was low for potassium and selenium (0–23%); intermediate for zinc, copper, and magnesium; low and intermediate for calcium in men and women, respectively; and low for iron in women. In conclusion, the diet followed by T1DM patients may not have a sufficient content of different micronutrients. Therefore, an adequate intake of low-fat dairy products, fish, legumes, and vegetables should be encouraged as components of a healthier dietary pattern.